Percepção de acadêmicos de licenciatura a respeito da disciplina de libras - Iachinski, Luci Teixeira (2017)
Brazilian Sign Language (Libras) officially became Brazil’s second language through Decree 5,626/2005. This law states that Libras must be part of the curriculum for undergraduate degree courses to train speech and language therapists and teachers. The main objective of this law was to prepare the professionals studying in these courses (even to a basic extent) to work with Deaf students in regular education classrooms. Consequently, the objective of this study was to analyze the perceptions of undergraduate students about Libras, with regard to organization, the importance of this language for their professional training, and their understanding of Libras and deafness. This was accomplished by surveying 59 students in undergraduate teaching courses at two private universities in southern Brazil who had already studied Libras but were still attending university. Data was collected through a questionnaire. The results showed that most participants did not have knowledge on these topics, nor deaf people, but nevertheless stated that Libras was important to their professional training. Furthermore, to these students, lecturers have a tendency to teach vocabulary and grammar in detriment of more comprehensive subjects regarding deafness, deaf people, and inclusion itself. Also, according to the students, Libras subject's course load should be longer, as a majority of them understand that a more extended course load could make them proficient in this language. We conclude that Libras as a subject is present in the universities, but that more investments in the area of deafness are necessary to make it more effective, particularly with regard to Libras as a subject; these would allow undergraduate students to move beyond simple contact with sign language as a linguistic system to broader discussions on educating Deaf students.